KONSTRUKSI FILSAFAT AKUNTANSI, DAN AUDITING STUDI ETNOGRAFI, DAN HERMENEUTIKA PADA CANDI PRAMBANAN JOGJAKARTA - Apollo Apollo (Dinasti Review, 2020)
The research resulted in the Reconstruction of Accounting Philosophy, and Auditing, Dialectical Approach, especially based on the Logic, Hermeneutic, Semiotic, and Rhetorical approaches. The originality of this research is the innovative philosophy of science in Indonesia. This research is expected to be the basis for the development of thinking through research on Ethnographic and Hermeneutic Studies at Prambanan Temple, Jogjakarta. Transubstantial Hermeneutics and semotics in Trimurti: Sang Hyang Wenang (Brahma), Sang Hyang Wening (Wisnu), Sang Hyang Guriang Tunggal (Siwa). In the third hermeneutic meaning (Trimurti) or Symbol, the ontological meaning is shifted or interpreted hermeneutically to become